An Examination of Executive Functioning in Young Adults Exhibiting Body-Focused Repetitive Behaviors. Issue 7 (July 2015) - Flessner, Christopher A.; Francazio, Sarah; Murphy, Yolanda E.; Brennan, Elle
<x xml:space="preserve">Abstract</x> Abstract Body-focused repetitive behaviors (BFRBs), including hair pulling, nail biting, and skin picking are repetitive, habitual, and compulsive in nature. Although characteristic of disorders such as trichotillomania and skin picking disorder, BFRBs are associated with other psychiatric conditions as well. To date, research has failed to examine neurocognitive risk factors, particularly executive functioning, implicated in BFRBs utilizing a transdiagnostic approach. The present study recruited 53 participants (n = 27 demonstrating BFRBs and n = 26 randomly selected controls) from a larger sample of young adults. Participants completed an automated neurocognitive test battery including tasks of cognitive flexibility, working memory, and planning and organization. Results revealed that participants in the BFRB group demonstrated significantly poorer cognitive flexibility (d = 0.63) than controls. No differences were noted in other neurocognitive domains. However, planning and organization demonstrated a significant relationship with various BFRB severity measures. Implications, limitations, and avenues for further research are discussed.